Odpowiedzi

  • Użytkownik Zadane
2010-02-14T13:44:21+01:00
A)(x²+1)-(x²-2)+10 =x²+1-x²+2+10=13

b)(a+4b)-(5+2a)-(3b-5)=a+4b-5-2a-3b+5=-a+b=0,1+0,2=0,3

c)(-a²+2ab-1)+ (a²-4ab+5)=-a²+2ab-1+a²-4ab+5=-2ab+4=-2*¼*2+5=1+5=6
2010-02-14T13:51:57+01:00
*-pomnożyć
1\4= 0.25

a) (2.2'+1)-(2.2'-2)+10=(4.84+1)-(4.84-2)+10=5.84-2.84+10=3+10=13
b) (-0.1+4*0.2)-{5+2*(-0.1)}-(3*0.2-5)=
(-0.1+0.8)-(5-0.2)-(0.6-5)=
0.7-4.8-4.4=-8.5
c)(-0.25'+2*0.25+2*2-1)+(0.25-4*0.25+4*2+5)=
(-0.25+2.5-1)+(0.25-5+5)=
1.25+0.25=1.5